The External Financing of Emerging Market Countries : Evidence from Two Waves of Financial Globalization - Zaklan, Aleksandar (IMF Working Papers; Working Paper ;, 2006)
We trace the history of where and why investors from the most advanced countries directed funds, ultimately helping finance economic development in emerging market countries. To do this, we analyze the determinants of international investors' willingness to hold the external liabilities issued by emerging market countries, through cross-country regressions for both prices (bond spreads) and quantities (bond market capitalization or stocks of external liabilities) estimated at various points during two waves of financial globalization (1870-1913 and the present time). The data are drawn from primary sources for the historical period, and the much-expanded, new vintage of the Lane and Milesi-Ferretti (2006) data set for the modern period. The results suggest that, throughout the past one and a half centuries, a combination of human capital (including informal human capital) and institutional quality has been a key determinant of emerging market countries' ability to attract international investors.